Pengaruh Komposisi Nutrisi Terhadap Laju Biodegradasi Styrofoam Menggunakan Ulat Hongkong (Larva Tenebrio Molitor) - Sri Armita Sari; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Styrofoam is a persistent plastic that is difficult to decompose naturally in the environment, is microplastic, which causes its accumulation as a major contaminant in soils, rivers and oceans. One method to process styrofoam waste is biodegradation. Biodegradation of styrofoam waste using mealworm (Tenebrio molitor larvae) was carried out by giving styrofoam as the main feed. The mealworm has been studied for their potential as decomposer of styrofoam due to best quality nutrient content. This study aims to increase the rate of biodegradation of styrofoam. Styrofoam waste used in this research is the type of Extruded Polystyrene (XPS) with variation of composition nutrients (tofu waste, bran, and yeast). The result showed that addition of bran nutrients could increase biodegradation rate by 27,26 mg/day with the highest percentage of 42,41% compared to other treatments for 28 days of observation.Keywords: styrofoam waste, biodegradation, mealworm, biodegradation rate, nutrition.